Nucleic acid hybridization on an electrically reconfigurable network of gold-coated magnetic nanoparticles enables microRNA detection in blood. Issue 11 (November 2018) - Tavallaie, Roya; McCarroll, Joshua; Grand, Marion; Ariotti, Nicholas; Schuhmann, Wolfgang; Bakker, Eric; Tilley, Richard; Hibbert, David; Kavallaris, Maria; Gooding, John
Abstract There is intense interest in quantifying the levels of microRNA because of its importance as a blood-borne biomarker. The challenge has been to develop methods that can monitor microRNA expression both over broad concentration ranges and in ultralow amounts directly in a patient's blood. Here, we show that, through electric-field-induced reconfiguration of a network of gold-coated magnetic nanoparticles modified by probe DNA (DNA–Au@MNPs), it is possible to create a highly sensitive sensor for direct analysis of nucleic acids in samples as complex as whole blood. The sensor is the first to be able to detect concentrations of microRNA from 10 aM to 1 nM in unprocessed blood samples. It can distinguish small variations in microRNA concentrations in blood samples of mice with growing tumours. The ultrasensitive and direct detection of microRNA using an electrically reconfigurable DNA–Au@MNPs network makes the reported device a promising tool for cancer diagnostics. An ultrasensitive miRNA sensor based on gold-coated magnetic nanoparticles modified with redox-labelled probe DNA is capable of detecting miRNA at a concentration of 10 aM to 1 nM in unprocessed blood, and following tumour-induced variation in miRNA levels.